2015
DOI: 10.1002/rnj.166
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Health Risks Associated with Prolonged Standing at Work and Intervention Effectiveness

Abstract: Purpose Prolonged standing at work has been shown to be associated with a number of potentially serious health outcomes, such as lower back and leg pain, cardiovascular problems, fatigue, discomfort, and pregnancy related health outcomes. Recent studies have been conducted examining the relationship between these health outcomes and the amount of time spent standing while on the job. The purpose of this article was to provide a review of the health risks and interventions for workers and employers that are inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
145
0
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(154 citation statements)
references
References 65 publications
3
145
0
6
Order By: Relevance
“…This fact is usual for nursing staff. It may cause foot pain, leg swelling, varicose veins, muscle fatigue, lower back pain, stiff neck and shoulders, and other health problems (16) . A study suggests the influence of psychosocial demands on the musculoskeletal system, pointing out that these cultural and psychosocial demands may affect sensitivity to pain, affecting the attention to symptoms and increasing the number of reports of symptoms of musculoskeletal disorders and/or perception of their causes (17) .…”
Section: Discussionmentioning
confidence: 99%
“…This fact is usual for nursing staff. It may cause foot pain, leg swelling, varicose veins, muscle fatigue, lower back pain, stiff neck and shoulders, and other health problems (16) . A study suggests the influence of psychosocial demands on the musculoskeletal system, pointing out that these cultural and psychosocial demands may affect sensitivity to pain, affecting the attention to symptoms and increasing the number of reports of symptoms of musculoskeletal disorders and/or perception of their causes (17) .…”
Section: Discussionmentioning
confidence: 99%
“…Employers should consider the following TWH concepts to reduce workers' sedentary time while at work [CDC 2014;Cifuentes et al 2015;OHSU 2014;NIOSH 2015d;Goetzel and Ozminkowski 2008;Morse et al 2012;Goetzel et al 2014;HHS 2008HHS , 2016Waters and Dick 2014;Robertson et al 2002;Grandjean 1988]:…”
Section: Concepts Into Workplace Safety and Health Programsmentioning
confidence: 99%
“…Prolonged standing can lead to venous disorders, back pain, and other musculoskeletal disorders [Waters and Dick 2014]. Grandjean [1988] notes how sitting and standing impose stress on different muscles, and therefore states that, "a workplace which allows the operator to sit or stand, as he wishes, is to be highly recommended from a physiological and orthopaedic point of view. "…”
mentioning
confidence: 99%
“…Despite this, research has shown that standing is also related to cardiovascular and musculoskeletal disorders (Waters & Dick, 2015). In both field (Andersen, Haahr, & Frost, 2007;Roelen, Schreuder, Koopmans, & Groothoff, 2008;Tissot, Messing, & Stock, 2009) and lab studies (Gallagher, Campbell, & Callaghan, 2014;Marshall, Patel, & Callaghan, 2011;Nelson-Wong & Callaghan, 2010b), low back pain (LBP) has been found in individuals required to perform prolonged static standing tasks.…”
Section: Introductionmentioning
confidence: 99%